A CRITICAL STUDY OF INTERVENTIONS TO INCREASE PHYSICAL ACTIVITY OF CHILDREN - Guzauskas, Donatas; Sukys, Saulius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
During the last decades, the physical activity (PA) of children decreased. Outdoor games have been replaced by the activities indoors that require less physical exercise and involve spending more time on sedentary behaviours. This article discusses not only the possible consequences of physical inactivity but also the possibilities of increasing PA. Related to this is the need to learn lessons from previous interventions to increase PA. The aim of this study is to critically investigate the interventions to increase PA of children. In order to reach this aim, the review and analysis of the scientific literature were carried out. The review has revealed that intervention can include educational programmes, new or improved policies, environmental improvements, or a health promotion campaign. The interventions that include several strategies are usually the most effective and result in a long-term change. They can be implemented in a variety of environments, including communities, workplaces, schools, healthcare and religious organizations. Those that involve a number of forms and multiple strategies are most effective. Physical education intervention programmes are increasingly recognized as a means of encouraging PA among children. Such programmes aim to expand the attractive environment for PA; reduce children's obesity; increase their physical capacity, and emphasize the importance of a systematic approach to increasing family and community engagement in the overall school physical activity programmes.